Stinson, ed. The Faces of Clio: An Anthology of Classics in Historical Writing from Ancient Times to the Present. - Isenberg, Michael (Teaching History: A Journal of Methods, 1990)
Review of The Faces of Clio: An Anthology of Classics in Historical Writing from Ancient Times to the Present.